Prospective evaluation of improving fluoroquinolone exposure using centralised therapeutic drug monitoring (TDM) in patients with tuberculosis (PERFECT): a study protocol of a prospective multicentre cohort study. Issue 6 (16th June 2020) - van den Elsen, Simone HJ; Sturkenboom, Marieke GG; Akkerman, Onno; Barkane, Linda; Bruchfeld, Judith; Eather, Geoffrey; Heysell, Scott K; Hurevich, Henadz; Kuksa, Liga; Kunst, Heinke; Kuhlin, Johanna; Manika, Katerina; et al.
Abstract : Introduction: Global multidrug-resistant tuberculosis (MDR-TB) treatment success rates remain suboptimal. Highly active WHO group A drugs moxifloxacin and levofloxacin show intraindividual and interindividual pharmacokinetic variability which can cause low drug exposure. Therefore, therapeutic drug monitoring (TDM) of fluoroquinolones is recommended to personalise the drug dosage, aiming to prevent the development of drug resistance and optimise treatment. However, TDM is considered laborious and expensive, and the clinical benefit in MDR-TB has not been extensively studied. This observational multicentre study aims to determine the feasibility of centralised TDM and to investigate the impact of fluoroquinolone TDM on sputum conversion rates in patients with MDR-TB compared with historical controls. Methods and analysis: Patients aged 18 years or older with sputum smear and culture-positive pulmonary MDR-TB will be eligible for inclusion. Patients receiving TDM using a limited sampling strategy (t=0 and t=5 hours) will be matched to historical controls without TDM in a 1:2 ratio. Sample analysis and dosing advice will be performed in a centralised laboratory. Centralised TDM will be considered feasible if >80% of the dosing recommendations are returned within 7 days after sampling and 100% within 14 days. The number of patients who are sputum smear and culture-negative after 2 months of treatment will be determined in the prospective TDM group and will be compared with the control group without TDM to determine the impact of TDM. Ethics and dissemination: Ethical clearance was obtained by the ethical review committees of the 10 participating hospitals according to local procedures or is pending (online supplementary file 1). Patients will be included after obtaining written informed consent. We aim to publish the study results in a peer-reviewed journal. Trial registration number: ClinicalTrials.gov Registry (NCT03409315 ).